(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This article provides an in-depth analysis of the origin and historical development of table tennis. It explores the early forms of the game, the evolution of its rules, and its global dissemination. Key milestones, such as the sport’s professionalization in the 20th century, the establishment of international federations, and its inclusion in the Olympic Games, are highlighted. The paper also examines the cultural and social significance of table tennis and its future trajectory.